Variation in Clinical Presentation, Metabolic Profile, Hormonal Parameters and Inflammatory Markers in Polycystic Ovary Syndrome Women with and without Polycystic Ovary Morphology Appearance - Sweekruti Jena; Ipsita Mishra; Anoj Kumar Baliarsinha; Debarchan Jena; Madhumita Debata (Journal of Human Reproductive Sciences)
Background: Polycystic ovary syndrome (PCOS) is a heterogeneous disorder with a spectrum of presentation. Studies have reported considerably different rates in terms of the incidence of polycystic ovary morphology (PCOM) in patients with PCOS with inconsistent results regarding the effects of PCOM in them. Aims: The aim of this study was to determine the differences in clinical presentation, metabolic profile, hormonal parameters and inflammatory markers in PCOS women with and without PCOM on ultrasonography (USG). Settings and Design: A total of 70 PCOS women were recruited. To analyse the differences between various parameters, the patients were divided into two groups based on the presence or absence of PCOM on USG of the pelvis as per the Rotterdam criteria. Materials and Methods: A total of 37 patients had PCOM as per the diagnostic criteria for PCOS (Group 1), while 33 patients did not have PCOM on USG and were designated as Group 2. All participants underwent a detailed clinical evaluation and biochemical investigations, including high-sensitivity C-reactive protein, serum adiponectin, luteinising hormone, follicle-stimulating hormone, total testosterone and serum anti-Mullerian hormone. The homeostasis model assessment of IR (HOMA-IR) was calculated using standard equations. Statistical Analysis Used: The mean and Standard deviation were computed for all continuous variables. Frequencies and proportions were calculated for categorical variables. Comparisons of the mean scores between the study groups were assessed using the Unpaired Student's t-test. The mean score of the subgroups was also compared using the unpaired Student's t-test. P < 0.05 was considered significant for all statistical inferences. Results: The mean LDL and mean triglyceride were higher in Group 2, which was statistically significant (P = 0.004 and P ≤ 0.001, respectively). The mean hs-CRP was found to be higher in Group 2, which was statistically significant (P = 0.005). The mean AMH was higher in Group 1, which was statistically significant (P = 0.002). Group 1 had higher adiponectin levels, which was statistically significant (P = 0.04). Conclusion: The above findings suggest that patients without diagnostic PCO morphology have a worse metabolic profile compared to those with PCO morphology on USG. Obese patients without PCO morphology probably have a higher cardiovascular risk compared to obese patients with PCO morphology.